Milk fatty acid signatures indicate both major and minor shifts in the diet of lactating Antarctic fur seals - SJ Iverson; John Arnould; IL Boyd (1997)
Fatty acid signature analysis is based on the principle that unique arrays of fatty acids within groups of organisms can be transferred, largely unaltered, up the marine food chain and thus may be an indicator of diet composition. We applied fatty acid signature analysis to milks collected from Antarctic fur seals (Arctocephalus gazella) at South Georgia in 1990-1991, during the perinatal period (N = 19) and subsequently during early (N = 11), mid (N = 11), and late (N = 8) foraging trips. In lactating otariid females, milk fatty acids secreted during the perinatal fast are derived largely from blubber mobilization and thus are influenced by dietary history prior to parturition. Conversely, milk fatty acids secreted during foraging trips are derived primarily from immediate dietary intake. The fatty acid signature of perinatal milks was significantly different from that of all other milks, suggesting differences in the prepartum diet when females are away from the breeding grounds. At the onset of foraging periods, the fatty acid composition of milks changed dramatically to reflect a diet composed mainly of krill. However, during late foraging periods, milk fatty acids again changed from those of early and mid foraging, and suggested a predominance of teleost fish in the diet. These findings were consistent with independent assessments of diet by faecal analysis and indicate the potential value of fatty acid signature analysis in studying foraging ecology in free-ranging pinnipeds.